National security policy in Ukraine: a change in the system of power relations of the modern world - V. Yakoviyk, Ivan (2020)
The article deals with the problems of finding ways to increase the effectiveness of government national security policy in the system of power relations of the modern world. The author reveals the essence and public administration nature of such phenomena as "national security of the state", "national security policy", "national security of Ukraine". The study analyzes the approaches to shaping modern national security policy of Ukraine, as well as its organizational and legal support. The system of the most urgent threats to the national security of Ukraine is revealed.